The Challenge of Debt Reduction during Fiscal Consolidation - Eyraud, Luc (IMF Working Papers; Working Paper ;, 2013)
Studies suggest that fiscal multipliers are currently high in many advanced economies. One important implication is that fiscal tightening could raise the debt ratio in the short term, as fiscal gains are partly wiped out by the decline in output. Although this effect is not long-lasting and debt eventually declines, it could be an issue if financial markets focus on the short-term behavior of the debt ratio, or if country authorities engage in repeated rounds of tightening in an effort to get the debt ratio to converge to the official target. We discuss whether these problems could be addressed by setting and monitoring debt targets in cyclically-adjusted terms.